Penerapan Nilai-Nilai Islami dan Relevansinya dengan Peningkatan Komitmen Kerja Karyawan - Febriani, Rizki; Asfiah, Nurul; Nurhasanah, Siti (Falah: Jurnal Ekonomi Syariah, 2019)
This study aims to analyze an effect of Islamic work ethics to Islamic work’s satisfaction and affective commitment women employees at restaurant in East Java. The Sample are 76 women employees that work at M2M and D’Mriah restaurant. Data analysis used Smart-PLS and Sobel as a mediation test. Result of this research showed there are positif and significant relationship between Islamic work ethic and Islamic work satisfaction, Islamic work ethic to affective commitment also Islamic work ethic to affective commitment through Islamic work satisfaction. Employees who implementing islmaic work ethic will fell satisfaction higher and this will increase affective commitment to organization. Effect Islamic work ethic directly to affective commitment higher than through Islamic work satisfaction.